Potential application for antimicrobial and antileukemic therapy of a flavonoid-rich fraction of Camellia sinensis. (October 2022) - de Souza, Mariana C.; de Souza Mesquita, Leonardo M.; Pena, Fabíola L.; Tamborlin, Leticia; da Silva, Laise C.; Viganó, Juliane; Antunes, Adriane E. Costa; Luchessi, Augusto D.; Duarte, Marta C. Teixeira; Barbero, Gerardo F.; Rostagno, Mauricio A.
Highlights: The PLE-SPE methodology is efficient to separate different classes of compounds. Antimicrobial effect of black tea flavonols on pathogenic microorganisms. Probiotic microorganismos were not impaired by tea flavonols. Black tea flavonols resulted in a blockade of the cell cycle in G0/G1. DNA fragmentation and altered the morphology of leukemic cells. Abstract: The antimicrobial and antileukemic effect of a purified fraction of flavonoids from the leaves of Camellia sinensis was evaluated. An extraction yield of 9.77 mg.g-1 total flavonoids was recovered through a pressurized liquid extraction associated with solid-phase extraction. This fraction was tested against pathogenic microorganisms ( Staphylococcus, Salmonella, and Enterococcus ), considering the minimum inhibitory concentration. In addition, the human monocyte cell line THP-1, derived from a patient with acute monocytic leukemia, was used for the antitumor assay. The results show that the flavonoid-rich fraction obtained by coupling a Pressurized Liquids Extraction in-line with a Solid Phase Extraction (PLE-SPE) has a high antimicrobial effect and resulted in cell cycle blockage G0 / G1, increased DNA fragmentation, and altered leukemic cell morphology. These results suggest that a flavonoid-rich fraction obtained from Camellia sinensis can be applied as potential adjuvants in chemotherapy treatment to mitigate the side effects caused by chemotherapy or even as a supplement to cancer therapy.